The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.bbadis.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Alkaptonuria is a novel human secondary amyloidogenic disease

Abstract: Alkaptonuria (AKU) is an ultra-rare disease developed from the lack of homogentisic acid oxidase activity, causing homogentisic acid (HGA) accumulation that produces a HGA-melanin ochronotic pigment, of unknown composition. There is no therapy for AKU. Our aim was to verify if AKU implied a secondary amyloidosis. Congo Red, Thioflavin-T staining and TEM were performed to assess amyloid presence in AKU specimens (cartilage, synovia, periumbelical fat, salivary gland) and in HGA-treated human chondrocytes and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 46 publications
9
93
0
Order By: Relevance
“…Finally, since we reported that AKU is an amyloidogenic disease (Millucci et al, 2012), at the best of our knowledge, the present work is the first associating chondroptosis and amyloidosis.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Finally, since we reported that AKU is an amyloidogenic disease (Millucci et al, 2012), at the best of our knowledge, the present work is the first associating chondroptosis and amyloidosis.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, ultra‐structural observations were complemented with biochemical and proteomic characterization of chondrocytes isolated from the ochronotic cartilage of AKU patients, indicating that AKU chondrocytes are characterized by HGA‐induced apoptosis, protein aggregation, nitric oxide release, and oxidative stress (Tinti et al, 2011a; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013). AKU patients have high levels of plasma serum amyloid A and pro‐inflammatory cytokines (Tinti et al, 2011b; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Millucci et al, 2014). The local expression of HGD in human osteoarticular system (Laschi et al, 2012) dramatically increases the effects in AKU cartilage degeneration.…”
mentioning
confidence: 99%
“…SAA amyloidosis is a serious complication of chronic inflammatory conditions such as rheumatoid arthritis, and its amyloid deposition process involves a cleaved product of the acute-phase protein serum amyloid A (SAA) (Momohara et al 2008). Indeed it was suggested that alkaptonuria is a novel-type II AA amyloidosis, if so will open new important perspectives for its therapy, particularly as methotrexate treatment significantly reduced in vitro HGA-induced amyloid A aggregates ( Millucci et al 2012).…”
Section: Pigmentation In Aku: the Nature Of The Pigmentmentioning
confidence: 99%
“…On the one hand, this would help in finding a dedicated cure for AKU, ochronotic arthropathy and other AKU-related severe organ complications; on the other hand, since AKU can be considered as a model for more common rheumatic diseases such as osteoarthritis and rheumatoid arthritis [53], the social and economic relevance of AKU study would definitely be much wider. In this light, developing in vitro and ex vivo models reproducing the disease condition becomes fundamental.…”
Section: Therapy Of Alkaptonuriamentioning
confidence: 99%
“…A range of human serum-, cell-and tissue-based human models have been established in the last years (schematically depicted in FIGURE 2) [30,[33][34][35]53,[60][61][62][63]. These human AKU models are based on exogenous addition of HGA range concentrations analogous to those found in AKU patients' plasma.…”
Section: Therapy Of Alkaptonuriamentioning
confidence: 99%